Foreign direct investment : trends, data availability, concepts, and recording practices - Patterson, Neil K.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This report surveys the recent state of FDI statistics at the international and national levels. It provides an overview of the available statistics on FDI and the concepts and definitions set out in international statistical manuals and country practices in implementing these guidelines.
Includes bibliographical references (p. 35-36).
nmn 14/05/13
Loans
Keywords: Investments, Foreign